An Investigation of Ground-Based GNSS Atmospheric Remote Sensing Techniques for Weather and Climate Monitoring in Nigeria - Combrinck, Ludwig (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.